Prevalence of type 2 diabetes and associated risk factors among Saharawi refugees in Algeria. (30th September 2020) - Henjum, S; Kjollesdal, M K R; Flaaten, M O; Andersen, E; Hjellset, V T; Morseth, M S
Abstract: Background: The Saharawi refugees have been living in refugee camps in the Algerian desert since 1975 and are dependent on food aid. A double burden of malnutrition by the coexistence of undernutrition among children and overweight and obesity among adults has been observed in the Saharawi refugee camps. Limited knowledge about the prevalence of type 2 diabetes (T2D) and associated risk factors exists in this population. The aim of this study was, therefore, to address this gap in the literature. Methods: A cross-sectional survey was carried out in five Saharawi refugee camps in Algeria in 2014. A total of 180 women and 175 men were included. HbA1c was used to assess the prevalence of T2D and prediabetes. The Finnish Diabetes Risk Score (FINDRISC) was used to estimate the risk of developing T2D. Multiple logistic regressions were performed to assess risk factors associated with T2D and prediabetes. Results: Median (min, max) HbA1c among the Saharawi refugees was 35 (4, 135) mmol/mol. The prevalence of T2D and prediabetes was 7% and 10%, respectively. The prevalence of overweight and obesity combined was 45%, and higher in women than in men. According to FINDRISC, 9% of participants had high risk of developing diabetes and 10% had moderate risk. In adjusted models, significant predictors for T2D were age, waist circumference and having a first-degree relative with T2D. Significant predictors for prediabetes were age, body mass index (BMI), waist circumference and a history of high blood glucose. Conclusions: We found moderate prevalence of diabetes and prediabetes and a relatively high prevalence of overweight and obesity among the Saharawi refugees, especially the women. Given the fragility of the Saharawi health care system, screening for diabetes should be conducted in a cost-effective manner and high-risk individuals should receive advice about lifestyle changes (e.g. diet and physical activity). Key messages: We found moderate prevalence of diabetes and pre-diabetes among the Saharawi refugees, and a high proportion were classified as overweight or obese. In light of this, the rates of T2D are likely to increase in the near future. The Saharawi health authorities should pay attention to the increased risk of diabetes in this vulnerable population.